Alveolar Epithelial Cells Promote IGF-1 Production by Alveolar Macrophages Through TGF-β to Suppress Endogenous Inflammatory Signals - Mu, Mimi; Gao, Peiyu; Yang, Qian; He, Jing; Wu, Fengjiao; Han, Xue; Guo, Shujun; Qian, Zhongqing; Song, Chuanwang (Frontiers in Immunology, 2020)
To maintain alveolar gas exchange, the alveolar surface has to limit unnecessary inflammatory responses. This involves crosstalk between alveolar epithelial cells (AECs) and alveolar macrophages (AMs) in response to damaging factors. We recently showed that insulin growth factor (IGF)-1 regulates the phagocytosis of AECs. AMs secrete IGF-1 into the bronchoalveolar lavage fluid (BALF) in response to inflammatory stimuli. However, whether AECs regulate the production of IGF-1 by AMs in response to inflammatory signals remains unclear, as well as the role of IGF-1 in controlling the alveolar balance in the crosstalk between AMs and AECs under inflammatory conditions. In this study, we demonstrated that IGF-1 was upregulated in BALF and lung tissues of acute lung injury (ALI) mice, and that the increased IGF-1 was mainly derived from AMs. In vitro experiments showed that the production and secretion of IGF-1 by AMs as well as the expression of TGF-β were increased in LPS-stimulated AEC-conditioned medium (AEC-CM). Pharmacological blocking of TGF-β in AECs and addition of TGF-β neutralizing antibody to AEC-CM suggested that this AEC-derived cytokine mediates the increased production and secretion of IGF-1 from AMs. Blocking TGF-β synthesis or treatment with TGF-β neutralizing antibody attenuated the increase of IGF-1 in BALF in ALI mice. TGF-β induced the production of IGF-1 by AMs through the PI3K/Akt signaling pathway. IGF-1 prevented LPS-induced p38 MAPK activation and the expression of the inflammatory factors MCP-1, TNF-α, and IL-1β in AECs. However, IGF-1 upregulated PPARγ to increase the phagocytosis of apoptotic cells by AECs. Intratracheal instillation of IGF-1 decreased the number of polymorphonuclear neutrophils in BALF of ALI model mice, reduced alveolar congestion and edema, and suppressed inflammatory cell infiltration in lung tissues. These results elucidated a mechanism by which AECs used TGF-β to regulate IGF-1 production from AMs to attenuate endogenous inflammatory signals during alveolar inflammation.